Flow of funds account in the Macedonian economy – methodology, trends and effects of the crisis - Gockov, GJorgji; KJosev, Sasho (CEA, Skopje, 2014)
The analyses of the macroeconomic developments mainly are based on the data from the basic macroeconomic accounts – national accounts, balance of payments, monetary survey, government statistics. Based upon theoretical grounds and international methodological principles and standards, an effort has been made for establishing and developing a consistent framework for analyzing flow of funds in the Republic of Macedonia. The matrices has been constructed and a quantitative analysis has been conveyed on the flows of financial funds amongst the sectors in the Macedonian economy for the period 2004-2013. Based on the constucted matrices, (1) the position of the each sector as a net debtor/creditor is assessed, (2) the sources for financing/investing of that position are analyzed, and (3) the flows of funds among the sectors are assessed. Special attention is given to the effects of the crisis, therefore two sub-period are distinguished and separately analyzed: 2004-2008 as a pre-crisis period and 2009-2013 as a post-crisis period. In these two sub-period the changes in the behavior of the main sectors of the Macedonian economy are analyzed in terms of their net lending/borrowing position and the sources of funding that position.
Keywords: national accounts, monetary survey, budget account, balance of payments, saving-investment gap, flow of funds account, crisis